Kontribusi Kompetensi Profesional dan Sosial Guru terhadap Hasil Belajar Siswa - Trisvi Trisvi; Aswardi Aswardi (Jurusan Teknik Elektro Fakultas Teknik Universitas Negeri Padang, 2022)
This research is correlational to find out how big the contribution of professional competence and social competence of teachers to the productive learning outcomes of class X TITL students at SMK N 1 Guguak. The quality of learning depends on the professional competence and social competence of the teacher. The purpose of this study is to determine the correlation between professional competence and social competence of teachers on productive learning outcomes. This type of research is correlational research. The research instrument is a questionnaire in the form of a Liekert scale that has been tested for validity and reliability. Based on the results obtained for each variable, there are 4 items that are invalid. The results of the professional competency test on productive learning outcomes are stated to be correlated, the results of social competence tests on productive learning outcomes are stated to be significantly related, while professional competency tests and social competences on productive learning outcomes are stated to be significantly related. The conclusion of this study is that professional competence, social competence, as well as professional competence and social competence on students' productive learning outcomes are stated to have a high correlation with the stated hypothesis being accepted.